The Impact of Using a Problem-Based Learning Approach on Students' Science Literacy in Class XI Natural Sciences and Mathematics on Reaction Rate Factor Material - Stephanie, Mian Maria (LAVOISIER: Chemistry Education Journal, 2023)
This study aims to determine the effect of applying the problem-based learning model on the literacy abilities of class XI MIA 3 students in the chemical reaction rate topic. This study used a classroom action research method for class XI students of SMAK 7 BPK PENABUR Jakarta, starting from August to October 2020. This classroom action research applied the Stephen Kemmis and Mc Taggart model. Through the results of the final test, observation, and journal reflection for two cycles, this study found that there was an increase in students' literacy skills. This study concludes that this learning model can be used to improve students' literacy skills if the teacher plans learning appropriately. Based on experience in conducting classroom action research, the researcher provides a number of suggestions to the teacher in applying this method.